Increased stillbirth rate during the second wave of COVID-19 pandemic in India. (November 2021) - Mahajan, Niraj N.; Gaikwad, Chaitanya; Tayshete, Rajashri; Saldanha, Cara; Pednekar, Rahi; Mahale, Smita D.; Gajbhiye, Rahul K.
Graphical abstract: Highlights: Stillbirth rate among COVID-19 pregnant women was higher in second wave (p = 0.038). Preeclampsia was reported higher during the second wave among stillbirths (p = 0.590). More stillbirths occurred at < 34 weeks gestation during the second wave (p = 0.214). Moderate-severe COVID-19 was observed only during the second wave among stillbirths. Reducing preventable stillbirths during COVID-19 pandemic should be global priority.